How to use corpora in language teaching - Sinclair, John (Studies in corpus linguistics, 2004)
After decades of being overlooked, corpus evidence is becoming an important component of the teaching and learning of languages. Above all, the profession needs guidance in the practicalities of using corpora, interpreting the results and applying them to the problems and opportunities of the classroom. This book is intensely practical, written mainly by a new generation of language teachers who are acknowledged experts in central aspects of the discipline. It offers advice on what to do in the classroom, how to cope with teachers' queries about language, what corpora to use including learner